2017
DOI: 10.1080/23774657.2017.1304811
|View full text |Cite
|
Sign up to set email alerts
|

Correcting the “Correctional” Component of the Corrections Officer Role: How Offender Custodians Can Contribute to Rehabilitation and Reintegration

Abstract: Research demonstrates that for many individuals imprisonment fails to rehabilitate or deter, and may actually promote recidivism. What can be done to limit reoffending and improve reentry experiences? One malleable component of custodial corrections is the role of the corrections officer. Alterations in the practices of detention workers may significantly contribute to positive offender outcomes. Drawing from several disparate literatures, this article proposes ten recommendations for how to reform the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 89 publications
1
21
0
Order By: Relevance
“…Findings from this study complement findings from other studies suggesting COs are supportive of collaboration with mental health staff and can play an important role in mental health care in corrections (Appelbaum et al, 2001; Schaefer, 2018). Developing best practices for mental health and custody staff, like we have for people living in the community, will offer guidance to prison administrators and providers about models to facilitate effective collaboration (Lamberti, 2016).…”
Section: Discussionsupporting
confidence: 83%
“…Findings from this study complement findings from other studies suggesting COs are supportive of collaboration with mental health staff and can play an important role in mental health care in corrections (Appelbaum et al, 2001; Schaefer, 2018). Developing best practices for mental health and custody staff, like we have for people living in the community, will offer guidance to prison administrators and providers about models to facilitate effective collaboration (Lamberti, 2016).…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, Logan and colleagues (37) highlight the importance of the staff-inmate relationship and state that officers can affect inmates' behavior positively and negatively during their incarceration (e.g. (38,39)). Taken together, these studies highlight the importance of investigating factors related to correctional officers in order to influence inmate's behavior, including misconduct.…”
Section: Discussionmentioning
confidence: 99%
“…As Weisburd, Farrington, and Gill (2016) found in their comprehensive review of systematic reviews much of the EBP literature is mixed and does better at revealing what programs or practices do or do not work at the highest level of understanding (i.e., a macro perspective), they do little to provide day-to-day practical guidance to practitioners (a.k.a., service delivery). However, core correctional practices programming has made progress in this area and targets the practices of correctional personnel more directly (Dowden & Andrews, 2004; see also Schaefer, 2017). Though considered preliminary, a recent meta-analysis of ten studies found significant reductions in recidivism when probation officers had received core correctional practices training compared to probationer populations supervised by officers without such training (Chadwick, Dewolf, & Serin, 2015).…”
Section: Discussionmentioning
confidence: 99%